Genetics and public health in the 21st century using genetic information to improve health and prevent disease - Khoury, Muin J.; Burke, Wylie; Thomson, Elizabeth J. (Elizabeth Jean), 1950- (New York ; Oxford : Oxford University Press, 2000)
In anticipation of the expected growth at the interface of genetics and public health, this book delineates a framework for the integration of advances in human genetics into public health practice.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Human Genome Project; Genetic screening; Public health; Medical genetics